Front Cover: Synthesis of 6‐Azaspiro[4.3]alkanes: Innovative Scaffolds for Drug Discovery (Eur. J. Org. Chem. 31/2017). Issue 31 (1st August 2017) - Chalyk, Bohdan A.; Isakov, Andrei A.; Butko, Maryna V.; Hrebeniuk, Kateryna V.; Savych, Olena V.; Kucher, Olexandr V.; Gavrilenko, Konstantin S.; Druzhenko, Tetiana V.; Yarmolchuk, Vladimir S.; Zozulya, Sergey; Mykhailiuk, Pavel K.
Abstract : The cover picture shows novel scaffolds for drug discovery, 6 azaspiro[4.3]alkanes, which have been synthesized by Enamine chemists (Ukraine, Kyiv). The synthesis starts from common four‐membered‐ring ketones, such as cyclobutanone, thienone, or N ‐Boc‐azetidinone, and includes only two chemical steps. The key transformation is the reaction between electron‐deficient exocyclic alkenes and in situ generated N ‐benzyl azomethine ylide. The high potential of the developed method was demonstrated by the novel synthesis of the central core of the known antibacterial agent DV‐7751. Details are discussed in the Full Paper by P. K. Mykhailiuk et al. on page 4530 ff (https://doi.org/10.1002/ejoc.201700536 ).